2015
DOI: 10.3390/min5040517
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Distribution of Respirable Dust After Blasting of Coal Roadway Driving Faces: A Case Study

Abstract: Coal roadway driving is an important part of the underground mining system, and very common in Chinese coal mines. However, the high concentration of respirable dust produced in the blasting operation poses a great hazard to miners’ health as well as the underground environment. In this paper, based on the direct simulation Monte Carlo method, the gas–solid two-phase flow model of particle movement is established to study the respirable dust distribution in blasting driving face. The results show that there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…People who work in such a production area are exposed to a high concentration of dust, which can cause pneumoconiosis or silicosis, either of which can seriously damage the miners' health [1]. It was reported that 57,000 miners were suffering from pneumoconiosis every year in China, with an average of 6000 miners dying each year [2,3]. Therefore, the research regarding dust control in mines has become a hot spot for many studies.…”
Section: Introductionmentioning
confidence: 99%
“…People who work in such a production area are exposed to a high concentration of dust, which can cause pneumoconiosis or silicosis, either of which can seriously damage the miners' health [1]. It was reported that 57,000 miners were suffering from pneumoconiosis every year in China, with an average of 6000 miners dying each year [2,3]. Therefore, the research regarding dust control in mines has become a hot spot for many studies.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional dust suppression methods include water spray and tarp coverage, which are unfavorable due to high cost and poor long-term dust suppression performance. Therefore, scholars in the international community have started to develop chemical-based dust suppression methods, which have proven to be promising in many dust suppression applications [18][19][20][21][22][23][24]. Overall, the chemical dust suppressant is highly favored considering its dust suppression effect, economic viability and environmental-friendliness, and therefore has a vast potential for future development [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of energy and operation costs and implementation of a carbon tax, a cost-effective ventilation and methane control strategy is strongly required for the mining industry, which means that the ventilation system should be designed to meet the regulatory limits and ensure a safe and productive working environment whilst keeping energy usage and operating costs to a minimum. As such, safety and cost are the two main competing requirements that have to be balanced, for which the careful ventilation design is mandatory and a concept of ventilation-on-demand has received considerable attention [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%